Effects of Reaction Conditions on MoS2 Thin Film Formation Synthesized by Chemical Vapor Deposition using Organic Precursor. (27th December 2016) - Ishihara, S.; Hibino, Y.; Sawamoto, N.; Ohashi, T.; Matsuura, K.; Machida, H.; Ishikawa, M.; Sudo, H.; Wakabayashi, H.; Ogura, A.
ABSTRACT: Molybdenum disulfide (MoS2 ) thin films were fabricated by two-step chemical vapor deposition (CVD) using (t-C4 H9 )2 S2 and the effects of temperature, gas flow rate, and atmosphere on the formation were investigated in order to achieve high-speed low-temperature MoS2 film formation. From the results of X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) investigations, it was confirmed that c-axis orientation of the pre-deposited Mo film has a significant involvement in the crystal orientation after the reaction low temperature sulfurization annealing and we successfully obtained 3 nm c-axis oriented MoS2 thin film. From the S/Mo ratios in the films, it was revealed that the sulfurization reaction proceeds faster with increase in the sulfurization temperature and the gas flow rate. Moreover, the sulfurization under the H2 atmosphere promotes decomposition reaction of (t-C4 H9 )2 S2, which were confirmed by XPS and density functional theory (DFT) simulation.